OC-034 Endoscopy in-situ simulation – improving nurse education and enhancing patient safety. (17th June 2017) - Ravindran, S; John, S; Dimmock, V; Murray, S; Wood, E
Abstract : Introduction: In-situ simulation is an immersive teaching modality that provides training for healthcare professionals in their own clinical environments, making learning more transferrable to the real world. This provides an integrated approach for developing technical and non-technical skills, that can enhance patient outcomes and additionally promote patient safety through latent error detection 1, 2 . We have introduced in-situ simulation into our endoscopy unit's nurse training timetable to promote educational development and reduce latent errors; it is estimated 2% of units do this 2 . We present a one year evaluation of our simulation programme (2016–17). Method: The in-situ programme was created through a collaboration between senior nursing staff, endoscopists and simulation faculty. Structured scenarios are designed around critical incidents, challenging cases and rare events that have occurred in the Endoscopy Unit. Low-fidelity manikins, iSimulate ALSi equipment and role-playing are used to deliver fortnightly sessions. Technical and non-technical learning objectives are explored through participant-led debriefs after each scenario. Faculty consists of a Gastroenterology Simulation Fellow and Senior Practice Development Nurse. Data is collected through questionnaires and free-text responses are thematically analysed. Latent errors are documented using a validated tool. Results: In total, we have collated 99 responses from 15 in-situ sessions. Participants include student nurses (4%), Band 2 (24%), Band 3 (13%), Band 5 (46%), Band 6 (9%) and Band 7+ (4%). All participants declared their personal learning needs were met; 97% 'agree' or 'strongly agree' that it was valuable to learn in their work environment. Overall, 95% 'agree' or 'strongly agree' that training will have a role in improving their clinical practice and 92% felt that training did not significantly disrupt clinical duties. Leadership and communication were strong emergent themes, particularly developing skills such as task allocation and effective handover. Many participants identified self-reflective practice and promotion of patient advocacy as important learning points. Latent errors were identified as outlined in Table 1 . Table 1 Risk stratification for identified latent errors (Risk score 1–3: Low risk; 4–6: Moderate Risk; 8–12 High Risk; 15–25: Extreme Risk; UCLP Latent Risk Identification Form). Conclusion: The integration of in-situ simulation into the education programme for endoscopy nurses promotes development of technical and non-technical skills and helps detect latent errors. This programme has now become embedded within nurse training in our unit with further content being developed and delivered. References: . Riley W, Lownik E, Parrotta C, Miller K, Davis S (2011) Creating High Reliability Teams in Healthcare through In situ Simulation Training. Adm. Sci. 1(1): 14-31. . Rosen MA, Hunt EA, Pronovost PJ et al (2012) In situ simulation in continuing education for the health care professions: a systematic review. J Contin Educ Health Prof . 32(4):243-54 Disclosure of Interest: None Declared